2018
DOI: 10.3390/catal8110556
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of a Membrane Micro Channel Reactor for Liquid Phase Direct Synthesis of Hydrogen Peroxide in Continuous Flow Using Nafion® Membranes for Safe Utilization of Undiluted Reactants

Abstract: In recent years, various modular micro channel reactors have been developed to overcome limitations in challenging chemical reactions. Direct synthesis of hydrogen peroxide from hydrogen and oxygen is a very interesting process in this regard. However, the complex triphasic process (gaseous reactants, reaction in liquid solvent, solid catalyst) still holds challenges regarding safety, selectivity and productivity. The membrane micro reactor system for continuous liquid phase H2O2 direct synthesis was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…To meet the safety regulations, most of the studies on the direct catalytic H 2 O 2 synthesis were performed with highly diluted gases in (semi-) batch reactors. 1,2 In addition, new and intrinsically safe concepts, that make use of membrane reactors 6,7 and electrochemical H 2 O 2 production, 3 have emerged. Recently, operando studies of the catalysts for H 2 O 2 production were reported by eliminating the explosion hazard by using thin capillaries as in situ reactors 8 or dissolving H 2 and O 2 at high pressures in separate liquid streams.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the safety regulations, most of the studies on the direct catalytic H 2 O 2 synthesis were performed with highly diluted gases in (semi-) batch reactors. 1,2 In addition, new and intrinsically safe concepts, that make use of membrane reactors 6,7 and electrochemical H 2 O 2 production, 3 have emerged. Recently, operando studies of the catalysts for H 2 O 2 production were reported by eliminating the explosion hazard by using thin capillaries as in situ reactors 8 or dissolving H 2 and O 2 at high pressures in separate liquid streams.…”
Section: Introductionmentioning
confidence: 99%
“…Sketch of the microstructured membrane reactor for the direct synthesis of H 2 O 2 with gas resaturation, adapted with permission from Ref. 15 (a) and detailed scheme of the arrangement of a FGE in a microchannel covered by a PDMS membrane, adapted with permission from Ref. 34 (b).…”
Section: Methodsmentioning
confidence: 99%
“…In the simulation, the flow regime present in the liquid channel was assumed to be laminar, due to the low liquid flow rates in the range of milliliters per minute as used in the concept presented in 6 and 15 as well as channel geometries in the millimeter range. The maximum expected Reynolds number Re calculated in a void rectangular channel with a width of 6 mm and a height of 1.97 mm for an estimated, elevated flow rate of 16 mL min −1 was 75, which confirmed the validity of this assumption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct synthesis of H2O2 is an attractive route that involves reacting both molecular hydrogen and oxygen over a palladium-based supported catalyst in contact with a liquid phase in a single process stage 17 . The process so far has only entered the pilot phase 18 . The main reason impeding a viable process is the low selectivity 19 .…”
Section: Introductionmentioning
confidence: 99%